Prkaa1 Metabolically Regulates Monocyte/Macrophage Recruitment and Viability in Diet-Induced Murine Metabolic Disorders - Yang, Qiuhua; Ma, Qian; Xu, Jiean; Liu, Zhiping; Zou, Jianqiu; Shen, Jian; Zhou, Yaqi; Da, Qingen; Mao, Xiaoxiao; Lu, Sarah; Fulton, David J.; Weintraub, Neal L.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Myeloid cells, including monocytes/macrophages, primarily rely on glucose and lipid metabolism to provide the energy and metabolites needed for their functions and survival. AMP-activated protein kinase (AMPK, its gene is PRKA for human, Prka for rodent) is a key metabolic sensor that regulates many metabolic pathways. We studied recruitment and viability of Prkaa1-deficient myeloid cells in mice and the phenotype of these mice in the context of cardio-metabolic diseases. We found that the deficiency of Prkaa1 in myeloid cells downregulated genes for glucose and lipid metabolism, compromised glucose and lipid metabolism of macrophages, and suppressed their recruitment to adipose, liver and arterial vessel walls. The viability of macrophages in the above tissues/organs was also decreased. These cellular alterations resulted in decreases in body weight, insulin resistance, and lipid accumulation in liver of mice fed with a high fat diet, and reduced the size of atherosclerotic lesions of mice fed with a Western diet. Our results indicate that AMPKα1/PRKAA1-regulated metabolism supports monocyte recruitment and macrophage viability, contributing to the development of diet-induced metabolic disorders including diabetes and atherosclerosis.